Records of epigeal spiders in Bahía Blanca, in the temperate region of Argentina - Zanetti, Noelia Inés (2016)
Ecological surveys of diversity and seasonal patterns of spiders in relation with cadavers have rarely been conducted, despite the high potential species diversity and abundance of spiders. The composition, abundance, guilds and seasonality of the spiders of Bahía Blanca, in the temperate region of Argentina were analysed. The study was performed in a semi-rural area between 2010 and 2011, using pitfall traps that were checked daily during 168 ± 7 days in winter, 38 days in spring, 30 days in summer, and 71 days in autumn. A total of 972 spiders were recorded belonging to 22 families and 65 species/morphospecies. The most abundant families were: Lycosidae, Zodariidae, Thomisidae, Theridiidae and Salticidae. The guild with more specimens was represented by ground hunters followed by specialists and ambush hunters, and the guild with the greatest number of species corresponded also to the ground hunters. Considering all specimens, adults prevailed with respect to juveniles, and males were more abundant than females. The more abundant species were Leprolochus birabeni, Steatoda sp. 1, Thomisidae sp. 33, Thomisidae sp. 32, Ostearius melanopygius and Metaltella simoni.